2022
DOI: 10.33448/rsd-v11i2.25611
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin and vinblastine induce apoptosis and impair migration in human cutaneous melanoma cells

Abstract: Cancer is an important cause of lethality, and melanoma is associated with less than 10% of survival. The traditional treatment includes the use of vinblastine, and it is associated with side effects. Curcumin is extracted from Curcuma longa rhizomes, and studied in many diseases, producing a variety of effects. We investigated the role of various cellular pathways concerning apoptosis, cell cycle enzymes in melanoma cell line SK-MEL-28, after treatment with curcumin, vinblastine, or a combination of both, for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…A recent experimental study verified that curcumin led human papillary thyroid carcinoma cells to apoptosis associated with endoplasmic reticulum stress 43 . Similar results were shown by Lunkes et al 44 who observed a significant increase in the levels of apoptosis of CM cells after treatment with 40 µM of curcumin for 24 h. For these reasons, we also searched for apoptosis induced by curcumin in CM cells. After 24 h of treatment, a significant increase in apoptotic cells at the highest concentration (100 µM) was detected.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…A recent experimental study verified that curcumin led human papillary thyroid carcinoma cells to apoptosis associated with endoplasmic reticulum stress 43 . Similar results were shown by Lunkes et al 44 who observed a significant increase in the levels of apoptosis of CM cells after treatment with 40 µM of curcumin for 24 h. For these reasons, we also searched for apoptosis induced by curcumin in CM cells. After 24 h of treatment, a significant increase in apoptotic cells at the highest concentration (100 µM) was detected.…”
Section: Discussionsupporting
confidence: 81%
“…Considering the results presented hitherto and to make this study more robust, we sought a plausible biochemical mechanism of action or signaling pathway that could explain the decrease in cell viability, apoptosis and the inhibition of cell migration. In this context, previous studies with CM reported that curcumin induces apoptosis by overproduction of ROS 12,40,44,48 . An interesting fact is that antineoplastic drugs act by exacerbating ROS levels, which induces apoptosis by activating the intrinsic pathway 49,50 .…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations